Development of English Innovation and Guidebook for Working Preparation about Hospitality Industry Concerning Tourism Services in ASEAN Community for Chomtong Industrial and Community Education College Students - Wongrukmitr, Nattaya (Community and Social Development Journal, 2020)
The research on “Development of English Innovation and Guidebook for Working Preparation about Hospitality Industry Concerning Tourism Services in ASEAN Community for Chomtong Industrial and Community Education College Students aimed to 1) construct an English innovation and guidebook using communicative approach to prepare about hospitality industry concerning Tourism Services in ASEAN Community for Chomtong Industrial and Community Education College Students and 2) find the difference between the students’ achievement before and after using English Innovation and Guidebook. The population were 29 2nd year Vocational Certificate students studying in the first semester, academic year 2017. The research instruments consisted of a questionnaire, 4 units of English Innovation with QR code and Guidebooks, and 30 items of English test . The data obtained were analyzed by using efficiency test, mean and standard deviation. The results were as follows: 1) The efficiency level of the English Innovation and Guidebook was at 76.03/75.75 2) The difference between students’ achievement before and after using English Innovation and Guidebook was 11.90.